A clinical case of a mixed testicular tumour with cryptorchidism in a dog of the Yorkshire Terrier breed - Nataliia Kanivets; Ihor Kolomak; Serhii Kravchenko; Nadiia Dmytrenko; Tetiana Burda (Наукові горизонти, 2023)
Histological examination of testicular tumours in cryptorchid males allows determining the nature of neoplasia, prognosis of long-term consequences in the form of metastases, and defining the optimal method of treatment of the animal, which determines the relevance of research in this area. The aim of the work is to determine the pathohistological structure of neoplasia of the left, cryptorchid, and morphology of the contralateral testes in a Yorkshire Terrier male with unilateral cryptorchidism. General clinical, ultrasonographic, radiological and histological methods were used in the examination of the animal. The article presents data on a mixed tumour of the intraperitoneal left testis of a 6-year-old Yorkshire Terrier, which is an atypical clinical case. It was found that the characteristic ultrasonographic features of the cryptorchid left testis tumour were numerous isoechoic foci of different diameters (from 4 to 26 mm), hyperechoic septa, and tuberous contours with a hyperechoic capsule. At laparotomy, the altered testis had an uneven surface saturated with blood vessels. The section showed milky-white neoplastic areas separated by fibrous bands that did not correspond to the normal structure of the organ. Histological examination of the parenchyma revealed areas of similar rounded cells in the form of a group of shapeless masses separated by a fibrous barrier. Neoplastic tubules had a developed fibrovascular stroma with an eosinophilic necrotic area. The protein membrane also had numerous fibrous formations. The layers of multifaceted cells were located perpendicular to the basal lamina, often with central necrosis, and the testicular mass contained multifocal haemorrhages. Such signs are characteristic of the lesion of Sertoli cells and interstitial Leydig cells, which indicated a mixed type of tumour of the left extraperitoneal testis of the Yorkshire Terrier. The contralateral right testis was unchanged and corresponded to the natural morphological and histological structure. The prostate was normal on macroscopic and histological examination, which has not been previously reported. Six-month follow-up of the dog showed no signs of metastatic process. The practical significance of the work is to obtain new scientific knowledge about the development of mixed tumours of the testis in cryptorchid males and the prospects for the treatment of diseased animals